GEOGRAPHY TEACHERS UNDERSTANDING IN IDENTIFYING LOW LEARNERS: SURVEY AND CLASSROOM OBSERVATION IN SURAKARTA - Sugiyanto Sugiyanto; Singgih Prihadi; Akbarudin Arif; Albertus Erico Jerry Krisna Nugroho; Nadya Putri Fitriani; Aldora Kusbiarsi (Universitas Sebelas Maret (UNS), 2026)
This study addresses the limited attention to teachers’ diagnostic abilities in identifying slow learners within subject-specific contexts, particularly in geography education. While previous research has emphasized inclusive education and differentiated instruction, there is still a lack of empirical evidence on how geography teachers understand and identify slow learners, especially in relation to the implementation of the Merdeka Belajar Curriculum in Indonesia. Therefore, this study aims to analyze geography teachers’ understanding of slow learners and examine the effect of Merdeka Curriculum training on their diagnostic abilities. A quantitative approach was employed involving 17 teachers from public public senior high schools in Surakarta. Data were collected through structured questionnaires and analyzed using descriptive statistics and simple linear regression. The results show that teachers’ understanding of slow learners falls within the moderate to high category, with noticeable variation across individuals and schools. Furthermore, the regression analysis indicates that Merdeka Curriculum training has a significant positive effect on teachers’ understanding (p = 0.005; β = 0.652). These findings highlight the importance of targeted professional development in strengthening teachers’ diagnostic competencies. This study contributes to the literature by providing empirical evidence from a geography education perspective and by demonstrating how curriculum-based training can support inclusive learning practices, particularly for students with slower learning progress.